Global assessment of leukemia care quality: insights from the quality of care index (QCI) from 1990 to 2021Research in context - Yuzhe Pan; Qian Liu; Nan Zhang; Shuang Peng; Xinqi Li; Fuling Zhou (EClinicalMedicine)
Summary: Background: While advancements in leukemia care have been made, the global quality of care remains a concern. This study utilizes a modified quality of care index (QCI) to assess the global status of leukemia care. Methods: We analyzed data from the global burden of disease (GBD) study spanning 1990–2021. The QCI was constructed using principal component analysis, based on the weighted variances of key indicators. We compared the original QCI with our modified version, analyzed QCI trends across different age groups and leukemia subtypes, identified key influencing factors using linear mixed models (LMM), and used spatial autocorrelation analysis to verify the autocorrelation of the socio-demographic index (SDI) region. Then we employed the bayesian age-period-cohort (BAPC) model to predict future QCI trends. Findings: Between 1990 and 2021, both the age-standardized incidence rate (ASIR) and age-standardized death rate (ASDR) for leukemia exhibited a consistent decline. Our modified QCI method outperformed the original approach, particularly when the variance explained by the first principal component was below 80%, demonstrating higher correlation with the healthcare access and quality index (HAQI) (Pearson r = 0.91 vs. 0.89) and improved explanatory power (R2 = 0.82 vs. 0.79). Over past three decades, QCI was highest in San Marino (97.72%) and lowest in Fiji (3.51%), with significant regional variations across SDI levels (F = 133.40, p < 2e-16). High-SDI regions had the highest QCI (78.50%; 95% confidence interval: 77.20%, 79.70%). QCI trends varied by age, peaking at 94.49% in the 15–19 age group in 2021 and declining to 0.44% in the 75–79 age group. LMM analysis identified sex, age, year, SDI region, and leukemia subtype as significant QCI determinants. Spatial autocorrelation analysis confirmed positive autocorrelation within SDI regions (Global Moran’s I = 0.87, p < 2e-16). Projections suggest a generally fluctuating upward trend in QCI for leukemia, reaching 79.58% by 2046. Interpretation: The QCI serves as an effective metric for evaluating the quality of leukemia care. Our findings reveal a strong association between leukemia QCI and regional economic and educational development. Age is a critical factor, with an aging population contributing to a potential decline in QCI. These results underscore the urgent need for targeted interventions to enhance health services for older adults and to improve care quality in economically disadvantaged regions. Funding: This study was supported by the National Natural Science Foundation of China (General Program) (No. 82370176) and the Key Research and Development Program of Hubei Province (No. CZKYXM2023036JZ).